1999
DOI: 10.1007/bf02882053
|View full text |Cite
|
Sign up to set email alerts
|

The giant panda (Ailuropoda melanoleuca) somatic nucleus can dedifferentiate in rabbit ooplasm and support early development of the reconstructed egg

Abstract: The giant panda skeletal muscle cells, uterus epithelial cells and mammary gland cells from an adult individual were cultured and used as nucleus donor for the construction of intenpecies embryos by transferring them into enucleated rabbit eggs. All the three kinds of somatic cells were able to reprogram in rabbit ooplasm and support early embryo development, of which mammary gland cells were proven to be the best, followed by uterus epithelial cells and skeletal muscle cells. The experiments showed that direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 12 publications
2
32
0
Order By: Relevance
“…Additionally, a pregnancy was observed after the transfer of embryos reconstructed from cells of argali Ovis ammon and enucleated oocytes of domestic sheep [71]. In the giant panda, blastocysts have also been obtained after nuclear transfer of panda cells into rabbit enucleated oocytes [12]. Furthermore, it has clearly been demonstrated that bovine oocyte cytoplasm could also serve as recipient for somatic cells from different mammalian species [16].…”
Section: Other Biotechnologies and Future Applicationsmentioning
confidence: 99%
“…Additionally, a pregnancy was observed after the transfer of embryos reconstructed from cells of argali Ovis ammon and enucleated oocytes of domestic sheep [71]. In the giant panda, blastocysts have also been obtained after nuclear transfer of panda cells into rabbit enucleated oocytes [12]. Furthermore, it has clearly been demonstrated that bovine oocyte cytoplasm could also serve as recipient for somatic cells from different mammalian species [16].…”
Section: Other Biotechnologies and Future Applicationsmentioning
confidence: 99%
“…gram Panda somatic nuclei and have supported development of nt-units to the blastocyst stage [12]. In this study, we tested rabbit oocyte cytoplasm as a means to reprogram human somatic cell nuclei, and demonstrate that the derived cells possess the properties and phenotypes of conventional human ES cells, that they retain a normal karyotype, and that they are capable of multilineage cellular differentiation.…”
Section: Introductionmentioning
confidence: 95%
“…For example, when cultures were switched, after retinoic acid induction, to a neuron-inducing medium composed of 6, 11, 14), human blood cells (lanes 2, 7), rabbit blood cells (lanes 4, 9, 15) or mouse feeders (lanes 3,8,12) were amplified by primer sets specific for human chromosome 7 alphoid repeats (lanes 1, 2, 3 The differentiated ntES cells derived from these fibroblasts. DNA samples were analyzed by multiplex PCR amplification of 14 microsatellite markers: 1, D3s1358; 2, vWA; 3, FGA; 4, Amelogenin; 5, D8s1179; 6, D21s11; 7, D18s51; 8, D5s818; 9, D13s317; 10, D7s820; 11, D16s539; 12, TH01; 13, TPOX; 14, CSF1PO.…”
Section: Somatic Differentiation Of Ntes Cellsmentioning
confidence: 99%
“…Even interspecies nuclear transfer has resulted offspring from a gaur (Lanza et al, 2002). Cows, rabbits, and sheep oocytes can support early development of embryos produced by nuclear transfer of somatic cell nuclei from other species (Chen et al, 1999;Dominko et al, 1999;White et al, 1999).…”
Section: Introductionmentioning
confidence: 99%